Regulation of SUMOylation Targets Associated With Wnt/β-Catenin Pathway - Fan, Linlin; Yang, Xudong; Zheng, Minying; Yang, Xiaohui; Ning, Yidi; Gao, Ming; Zhang, Shiwu (Frontiers in Oncology, 2022)
Wnt/β-catenin signaling is a delicate and complex signal transduction pathway mediated by multiple signaling molecules, which plays a significant role in regulating human physiology and pathology. Abnormally activated Wnt/β-catenin signaling pathway plays a crucial role in promoting malignant tumor occurrence, development, recurrence, and metastasis, particularly in cancer stem cells. Studies have shown that the Wnt/β-catenin signaling pathway controls cell fate and function through the transcriptional and post-translational regulation of omics networks. Therefore, precise regulation of Wnt/β-catenin signaling as a cancer-targeting strategy may contribute to the treatment of some malignancies. SUMOylation is a post-translational modification of proteins that has been found to play a major role in the Wnt/β-catenin signaling pathway. Here, we review the complex regulation of Wnt/β-catenin signaling by SUMOylation and discuss the potential targets of SUMOylation therapy.